Development and Evaluation of an intelligent Q&A chatbot system for the medical aesthetics domain - Gamayun, Igor; Ivashchenko, Oksana; Zhou, Gang (LLC SPC "InterConf", 2024)
In recent years, the medical aesthetics industry has experienced rapid growth, becoming a focal point for individuals concerned with their appearance and self-image. This surge in interest has led to an increased demand for information and services related to medical aesthetics. The traditional consultation methods, including phone consultations, online chats, and face-to-face meetings, present such challenges as limited availability of experienced professionals, extended waiting times, and failing to meet users' expectations for prompt responses. This article presents development an intelligent Q&A chatbot system tailored to the medical aesthetics domain which should meet users' needs for precise and real-time advice. By employing NLP and deep learning technologies, we seek to create a model to understand user questions and deliver precise answers. The developed system consists of several modules such as User Interface, Intelligent Q&A System, Knowledge Base, Data Processing, and Pre-trained Model for Medical aesthetics.
Keywords: medical aesthetics; intelligent chatbot; API; natural language processing; BERT